Advancements in microalgae-mediated technologies for antibiotic removal from wastewater: a review - Neha Pathania; Swati Kumari; Kamlesh Thakur; Saurabh Kulshrestha; Rohit Khargotra (Biodegradation, 2026)
The development of efficient systems for removing antibiotics from wastewater is being pushed by increase in antibiotic resistance brought on by the environmental discharge of antibiotics. Antibiotic were not completely eliminated using conventional technologies like activated sludge, constructed wetland systems and many other procedures. A viable alternative for treating wastewater through adsorption, accumulation, biodegradation, photodegradation, and hydrolysis has recently been investigated using microalgae-based technology. This review focuses on effects of antibiotics on microalgae, as well as the ways in which microalgae remove antibiotics and how they work with other technologies to do so, including photocatalysis, advanced oxidation, and complementary microorganism degradation. The physiochemical and operational parameters like pH, temperature, light intensity and many more which influence the elimination of antibiotics in the wastewater treatment system. Future research requirements, further opportunities, the limitations of the available microalgae-based technologies were also discussed.

Harnessing SDS as a source of sulfur: a bioremediation strategy of Fischerella sp. lmga1 - Ankit Srivastava; Anirbana Parida; Samujjal Bhattacharjee; Neha Gupta; Satya Shila Singh; Arun Kumar Mishra (Biodegradation, 2025)

Developing a microbial community structure index (MCSI) as an approach to evaluate and optimize bioremediation performance - Jeff Gamlin; Renee Caird; Neha Sachdeva; Yu Miao; Claudia Walecka-Hutchison; Shaily Mahendra; Susan K. De Long (Biodegradation, 2024)

Optimized culture conditions facilitate the estrone biodegradation ability and laccase activity of Spirulina CPCC-695 - Neha Sami; Tasneem Fatma (Biodegradation, 2023)

Laboratory and field scale bioremediation of hexachlorocyclohexane (HCH) contaminated soils by means of bioaugmentation and biostimulation - Nidhi Garg; Pushp Lata; Simran Jit; Naseer Sangwan; Amit Kumar Singh; Vatsala Dwivedi; Neha Niharika; Jasvinder Kaur; Anjali Saxena; Ankita Dua; Namita Nayyar; Puneet Kohli; et al. (Biodegradation, 2016)

Functional screening of enzymes and bacteria for the dechlorination of hexachlorocyclohexane by a high-throughput colorimetric assay - Pooja Sharma; Swati Jindal; Kiran Bala; Kirti Kumari; Neha Niharika; Jasvinder Kaur; Gunjan Pandey; Rinku Pandey; Robyn J. Russell; John G. Oakeshott; Rup Lal (Biodegradation, 2014)